The influence of charge on the multiple thermal transitions observed in xanthan. (December 2019) - Abbaszadeh, A.H.; Lad, M.; Morris, G.A.; MacNaughtan, W.; Sworn, G.; Foster, T.J.
Abstract: Helix-coil transitions in xanthans occur at lower temperatures when the pyruvate group is charged, destabilising the polymer chains. Increasing salt content increases the transition temperature by reducing the effective charge on the pyruvate. A simple equivalent mass action model predicts how transition temperatures change as a function of salt concentration. The functional form of the change in transition temperature (1/T) versus natural log (salt concentration) is approximately linear and similar to more traditional polyelectrolyte theories. Transition temperatures in xanthans containing nominally homogeneous pyruvate contents show biphasic transitions, this is because the phases contain different pyruvate levels, however the transitions approach one another in temperature and eventually merge as salt content is increased. It is proposed that pyruvate groups, despite being present at a lower concentration relative to glucuronic acid, dominate the charge interactions due to their location on the outside of the helices. (143 words). Graphical abstract: Image 1 Highlights: Transitions in xanthan with charged pyruvate groups occur at lower temperatures. A mass action model describes changes in transition temperature with salt addition. Xanthans having biphasic transitions have phases with different levels of pyruvate. Salt differentially affects transition temperatures of different pyruvate phases. A linear relation exists between ln[NaCl] and the reciprocal transition temperature.